Biochemical Studies on Phenylhydrazine Induced Experimental Anemic Albino Rats - Madhikarmi, Nirjala Laxmi; Murthy, Kora Rudraiah Siddalinga (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: The present study evaluated the modulatory effects of diphenylhydrazine induced experimental wistar albino rats and also to assess various biochemical parameters in whole blood and red blood cell lysate. MATERIALAND METHODS: Twenty male albino rats weighing 180-200 gm were selected for the study and divided in two groups; ten phenylhydrazine dihydrochloride (PHZ) induced anemia and ten healthy control. Thiobarbituric acid reactive substances and lipid hydroperoxide were measured as lipid peroxidation parameter. The antioxidant vitamins A, C and E and enzymatic antioxidants; catalase, glutathione peroxidase and superoxide dismutase were also assessed. RESULTS: Phenylhydrazine induced anemic rats showed a significant increase in the lipid peroxidation and decrease in the antioxidants as compared to healthy rats. CONCLUSION: The study concludes that phenylhydrazine induced experimental anemic albino rats showed increased oxidative stress than compared with healthy albino rats. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 41-47